Situated web portal for local awareness and transient interaction - José, Rui (2004)
When used as part of a larger ubiquitous computing infrastructure, public displays have a great potential for enriching transitional spaces. They can enable brief encounters with information that is relevant for their specific situation, improving local awareness, promoting information sharing and enabling new and much engaging user experiences. The research presented in this paper introduces the concept of situated portal as being a web portal of situational relevant information, targeted for the public display and using large screens or wall projections,. In this paper we will briefly describe the architecture of our system, our initial prototype and our early results. Building in our experience of creating this system we then describe some of the main open issues that we plan to address in a multi-disciplinary research project.